2020
DOI: 10.3390/en13112855
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Analysis of One-Stop Charging Stations for Battery and Fuel Cell EV with Renewable Energy Sources

Abstract: Currently, most of the vehicles make use of fossil fuels for operations, resulting in one of the largest sources of carbon dioxide emissions. The need to cut our dependency on these fossil fuels has led to an increased use of renewable energy sources (RESs) for mobility purposes. A technical and economic analysis of a one-stop charging station for battery electric vehicles (BEV) and fuel cell electric vehicles (FCEV) is investigated in this paper. The hybrid optimization model for electric renewables (HOMER) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 11 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Note that regarding zero emission electric vehicles, BEVs technology commonly shown as a competitor to FCVs solution [71] whereas they are complementary both in terms of use [72] and distribution. Regarding the latter point, Bansal et al demonstrated that combining BEV and FCV charging in a single station was the optimal design solution both in terms of cost and grid infrastructure.…”
Section: H 2 Distributionmentioning
confidence: 99%
“…Note that regarding zero emission electric vehicles, BEVs technology commonly shown as a competitor to FCVs solution [71] whereas they are complementary both in terms of use [72] and distribution. Regarding the latter point, Bansal et al demonstrated that combining BEV and FCV charging in a single station was the optimal design solution both in terms of cost and grid infrastructure.…”
Section: H 2 Distributionmentioning
confidence: 99%
“…During the late 1960s and the early 1970s, there was a gas shortage, which provoked EV [75]. However, because of its expense, a limited number of charging stations, and lack of power supply, it was unpopular [76]. Though this technology has several advantages, it also has a few negative points.…”
Section: Battery Electric Vehiclesmentioning
confidence: 99%
“…Figure 16 shows a schematic of a BEV and its main components [78]. Moreover, Figure 17 summarizes the top reasons why people do not buy an electric vehicle [76].…”
Section: Battery Electric Vehiclesmentioning
confidence: 99%
“…Foreign countries attach great importance to the economic research of hydrogen energy storage technology and windpower HESS and have begun to develop the evaluation simulation software of wind-power HESS, including the following three software platforms: first, HOMER, a power system optimization platform developed by the Renewable Energy Laboratory of the United States Department of Energy, is mainly used to evaluate the effect of grid-connected power generation system and can effectively assess and analyze the economy and sensitivity of the integrated system of wind power and fuel cells hydrogen production (Bansal et al, 2020;Hassani et al, 2020). Second, TRNSYS, a system dynamic behavior simulation software platform designed and released by the New Energy Power Laboratory of the University of Wisconsin-Madison, United States, effectively quantifies and evaluates the operation effect of power system through simulation, and its standard database is composed by nearly 150 calculation models, including the simulation calculation models of hydrogen production system by wind power and fuel cell generation models (Bakić Vukman et al, 2012;Buonomano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%